2012
DOI: 10.7324/japs.2012.2507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leave extract of Ocimum basilicum on deltamethrin induced nephrotoxicity and oxidative stress in albino rats

Abstract: Deltamethrin is a pyrethroid insecticide used extensively in pest control. On the other hand it showed different toxicity in mammalian animals. Basil or sweet basil (Ocimum basilicum) is a plant which showed many pharmacological effects. The present work studied the potential protective effect of Ocimum basilicum extract on deltamethrin-induced nephrotoxicity in albino rats. Treating animals with deltamethrin induced several histopathological alterations in the kidney. The renal tubules lost their characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
42
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 29 publications
16
42
0
4
Order By: Relevance
“…Antioxidant enzymes (SOD and CAT) are the first line of defense against free radical induced oxidative stress. Superoxide dismutase is used for catalytic dismutation of superoxide radicals to hydrogen peroxide, while catalase is responsible for the catalytic decomposition of hydrogen peroxide to oxygen and H 2 O [30]. Our results regarding the oxidative hepatic tissue damage in DLMinduced toxicity which manifested by a significant elevation in the liver tissue MDA concentration with reduction of tissue CAT and SOD when compared to the control group.…”
Section: Discussionsupporting
confidence: 48%
“…Antioxidant enzymes (SOD and CAT) are the first line of defense against free radical induced oxidative stress. Superoxide dismutase is used for catalytic dismutation of superoxide radicals to hydrogen peroxide, while catalase is responsible for the catalytic decomposition of hydrogen peroxide to oxygen and H 2 O [30]. Our results regarding the oxidative hepatic tissue damage in DLMinduced toxicity which manifested by a significant elevation in the liver tissue MDA concentration with reduction of tissue CAT and SOD when compared to the control group.…”
Section: Discussionsupporting
confidence: 48%
“…This finding came in accordance with previous studies which reported that DM significantly decreased the antioxidant defense [9,15,28,29]. Also DM intoxication caused significant increase in NO concentration [ Table-2].…”
Section: Discussionsupporting
confidence: 82%
“…Ocimum basilicum, popular known as Basil or Sweet Basil, is a common herb that belongs to Lamiaceae family. Studies have shown many pharmacological effects in several diseases, with potent antioxidant, anti-aging, anticancer, antiviral, and antimicrobial properties (Sakr, Al-Amoudi, 2012). Studies have reported that rosmarinic acid (RA) is the most biologically active compound present in Basil related to this activities (Javanmardi et al, 2002;Lee, Scagel, 2009;Shiga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%